Tax on industry and commerce in the municipality of San Juan de Rioseco-Cundinamarca (2014)
Using the article 287 of the Constitution politics in Colombia: the territorial entities enjoy autonomy for the management of their interests within the limits of the Constitution and the law and paragraph 9 of article 95 of the Constitution stipulates the duties and obligations of persons and citizens to the Constitution and law specifically "contribute to the operating expenses and investment of the State within the concepts of Justice and equity". Therefore the municipalities set taxes within their jurisdiction in order to raise revenue that will enable it to comply with its territorial functions.